Can liquidity shifts explain the lockup expiration effect in stock returns? - KRISHNAMURTI, Chandrasekhar (Institutional Knowledge at Singapore Management University, 2009)
Several studies on the expiration of IPO lockups document a strong negative reaction even though the unlock event is devoid of any informational content. The empirical finding has remained a conundrum. In this paper, we find that changes in liquidity can account for the observed stock price reaction around lockup expiration. Specifically, firms which show improvement in liquidity subsequent to the unlock day experience positive abnormal returns in the post-expiration period, and vice versa. Another interesting conclusion that emerges from our research is that liquidity changes can predict future abnormal returns. Our results remain robust to the use of alternate procedures to characterize unexpected changes in liquidity.